Improving our understanding of childhood psoriasis: Identifying opportunities for early intervention for the prevention of long-term harm - Burden-Teh, Esther (2020)
1.1 Introduction Psoriasis is an immune-mediated chronic inflammatory disease affecting the skin and joints of adults and children. This PhD focused on psoriasis in children because it is especially for this age group that both a research need and an opportunity to improve long-term health outcomes exist. There is a deficiency of paediatric specific research to guide optimal management and, for many individuals, the persistence of psoriasis into adulthood has a negative cumulative effect over their lifetime. Difficulties can arise because of the physical, psychological, and social burden of psoriasis, including the development of psoriatic arthritis.